Zapatrywania ekonomiczne Václava Havla w kontekście bezpieczeństwa gospodarczego i geopolitycznego Europy Środkowo-Wschodniej. Część 1 - Oleksiuk, Adam (Przegląd Wschodnioeuropejski, 2023)
The work presents the profile of Václav Havel (1936-2011), a famous Czech writer and playwright, dissident, anti-communist activist, one of the co-authors of Charter 77, the ninth and last president of Czechoslovakia (1989-1992), and the first president of the Czech Republic (1993-2003). This article aims to present the economic views, not of an economist, but of an eminent Czech statesman and a leading representative of Central and Eastern Europe popularized during his tenure as the president of Czechoslovakia.